Comprehensive Physiology 1992
DOI: 10.1002/cphy.cp080248
|View full text |Cite
|
Sign up to set email alerts
|

Renal Excretion and Tubular Transport of Organic Anions and Cations

Abstract: The sections in this article are: Organic Anions Introduction Renal Excretion and Tubular Transport of Organic Anions Mechanisms Involved in Tubular Transport of Organic Anions Conclusions on the Renal Transport of Organic Anions Organic Cations Introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 410 publications
1
35
0
Order By: Relevance
“…Transport of para-aminohippurate (PAH) is a prototype of organic anion secretion in the proximal renal tubule [19,21,23,35]. Its contraluminal uptake step, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Transport of para-aminohippurate (PAH) is a prototype of organic anion secretion in the proximal renal tubule [19,21,23,35]. Its contraluminal uptake step, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…rOCT1 is the first member of a new, rapidly growing protein family (2, 4 -10) that belongs to a major superfamily of transmembrane facilitators (12). The OCT family includes a second subtype, OCT2 (2,9), and the polyspecific renal anion transporter OAT1, which is known as the paraaminohippurate transporter (10,11,13). rOCT1 probably mediates the first step in the excretion of many organic cations in the kidney, small intestine, and liver, since it was localized in the basolateral membrane of renal proximal tubules and intestinal enterocytes and in the sinusoidal membrane of hepatocytes (14).…”
mentioning
confidence: 99%
“…Indeed, it is frequently assumed that interac tion of a molecule with the basolateral OC transporter simply requires that the com pound possesses a net positive charge [see 21,24], It is significant, therefore, that Ullrich and Rumrich [25] have found that interaction of the transporter with organic bases does not display a pH sensitivity consistent with the binding of substrate being limited to the protonated species. This led to his suggestion that the OC transporter senses the substrate's di pole structure and/or its ability to form hydro gen bonds, rather than the degree of ioniza tion.…”
Section: Specificity O F Basolateral Oc Transportmentioning
confidence: 99%